Antiinflammatory Treatment Ameliorates HPA Stress Axis Dysfunction in a Mouse Model of Stress Sensitivity - Gerber, Alexis R. (Endocrine Society, 2012)
Dysregulated stress responsivity is a hallmark of neuropsychiatric disease. The regulation of stress activation and recovery involves tight coordination between neuronal and glial networks. At a certain threshold of sensitivity, stress exposure can evoke a neuroimmune response. Astrocytes are potential mediators of these effects because they are able to respond to neuroimmune effector molecules and regulate neuronal activity. Mice deficient in corticotropin-releasing factor receptor-2 display increased stress sensitivity and are therefore a useful model in which to examine the intersection of neuroimmune activation and stress pathway dysregulation. We hypothesized that a component of elevated stress reactivity may involve an engagement of neuroimmune effectors, including astrocytes. Therefore, we hypothesized that this phenotype may be rescued by concomitant nonsteroidal antiinflammatory drug (NSAID) treatment. To examine this, mice exposed to chronic stress were treated with NSAID in their drinking water, and changes in hypothalamic-pituitary-adrenal stress axis function were examined. As a correlate of altered astrocyte function, levels of glial fibrillary acidic protein were measured. Supportive of our hypothesis, NSAID treatment rescued the hypothalamic-pituitary-adrenal stress axis dysfunction in stress-sensitive corticotropin-releasing factor receptor-2(−/−) mice and also reversed the stress-induced increase in glial fibrillary acidic protein in stress-regulating brain regions including the paraventricular nucleus of the hypothalamus, ventral hippocampus, and prefrontal cortex. These findings support the local involvement of astrocytes in the exacerbation of stress pathway dysregulation. The specificity of these effects in a stress-sensitive genotype highlights the importance of utilizing a model of stress dysregulation in the examination of factors that may translate to neuropsychiatric disease.